The observed guard dogs’ proximity to goats and horses. - Konstanze Krueger (6750239) (2025)
a) Snapshot from observations at farm 5: while the female dog (far left, red circle) stayed in close contact with a horse, her offspring kept a distance of 3 horse body lengths to the closest horse. Reprinted under a CC BY 4.0 license, with permission from Sarah Handel, original copyright 2025. b) Proximity graph of the frequencies the dogs (red) stayed in close contact with horses (green) at farm 5: while the female dog (dog1) was observed in close contact with three horses once, her offspring (dogs 2–5) were never seen in close contact with any horse. c) Proximity categories of dogs to livestock at farm 1–5, in frequencies per hour: the proximity was categorised in 1-3 body lengths, in 1 body length, and in contact with a farm animal. The dogs stayed less in direct contact with the farm animals (a) than within one body length (b) (Wilcoxon signed rank tests: N = 19, V = 0, p = 0.009).